The Degree of Practicing Strategic Planning Skills by Academic Leaders at King Khalid University from the Perspective of the Faculty Members - Sultan Saeed Abdo Al-Mekhlafi (University of Science and Technology, Yemen, 2020)
This study aimed to identify the degree of practicing strategic planning skills by the academic leaders at King Khalid University from the perspective of the faculty members of the university. It also aimed to identify any differences attributed to the variables of specialization, gender of the respondent, scientific rank, number of service years at the university. The researcher used the descriptive method on sample of (326) faculty members at King Khalid University in the first semester of the academic year 39 / 1440AH, which were randomly selected and represented (16.11%) of the population (2024) members. The results showed that the mean of practicing degree of the strategic planning skills by the academic leaders at King Khalid University was significantly achieved by a high degree, with an average of (3.57) and by (71.30%) of the total degree of practice. The results showed no statistically significant differences in the average of practicing degree of strategic planning skills according to the variables: scientific rank, gender. However, there were statistically significant differences according to the variables of specialization in favor of the applied sciences, the number of service years, and in favor of those who had more years of service.  It was recommended that professional development of the leaders of colleges and academic departments should continue to strengthen their skills in strategic planning so as to achieve the vision of King Khalid University 2030, to be among (200) universities in the world. Keywords: planning skills, strategic planning, academic leaders.